2010
DOI: 10.1051/0004-6361/200912549
|View full text |Cite
|
Sign up to set email alerts
|

On emission-line spectra obtained from evolutionary synthesis models

Abstract: Aims. In this paper we study the influence of the ionizing cluster mass on the emission line spectrum of H ii regions in order to determine the influence of low mass clusters on the integrated emission line spectra of galaxies. Methods. For this purpose, we present a grid of photoionization models that covers metallicities from Z = 0.001 to Z = 0.040, ages from 0.1 to 10 Ma (with a time step of 0.1 Ma), and cluster initial masses from 1 to 10 7 M . The stellar masses follow a Salpeter initial mass function (IM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Based on a first approximation, taking into account the models presented in Villaverde et al (2010), those high equivalentwidth galaxies in [O iii] λ5007 may be an analogous to our detected emitters with high [O ii]3727 equivalent width.…”
Section: [O Ii]3727 Equivalent Widthmentioning
confidence: 68%
See 1 more Smart Citation
“…Based on a first approximation, taking into account the models presented in Villaverde et al (2010), those high equivalentwidth galaxies in [O iii] λ5007 may be an analogous to our detected emitters with high [O ii]3727 equivalent width.…”
Section: [O Ii]3727 Equivalent Widthmentioning
confidence: 68%
“…They found that those galaxies can be classified as: low-mass, strong starbust, and compact. Following the models of Villaverde et al (2010), we can assume a maximum equivalent width of the [O ii]3727 line for 'normal' galaxies at 150 Å. Indeed, Kong et al (2002) found that galaxies with EW[O ii]3727>100 Å are in the 90th percentile and Thomas et al (2013), based on data from the SDSS-III/BOSS, showed that galaxies with EW[O ii]3727>100 Å are located outside the limits of their figures.…”
Section: [O Ii]3727 Equivalent Widthmentioning
confidence: 99%
“…An extra caveat arises for clusters with stellar masses of < ∼ 10 4 M since in this regime the Initial Mass Function is not properly sampled and stochastic effects are important (e.g. Villaverde et al 2010).…”
Section: On the Relationship Between Extra N And Wr Starsmentioning
confidence: 99%
“…Given that the continuum shape and luminosity control the emission line intensity in a non-linear way (see Villaverde et al 2010, for more details), using an average ionizing continuum of clusters in function of the cluster mass as input of photoionization codes, as synthesis models provide, gives unrealistic results.…”
Section: Effects In H II Regionsmentioning
confidence: 99%